Opposition by imitation: the economics of Italian Anti-Mafia activism - Jerne, Christina (Diverse Economies and Livable Worlds Series, 2025)
"Opposition by Imitation explores anti-mafia activism in Italy, revealing how ordinary people resist, counter, and prevent criminal economies from proliferating both by creating alternative economies and by subversively adopting business tactics similar to the mafia's. Exposing the political implications of this mimetic opposition, Christina Jerne points to its potential impact on crime prevention and criminalization, both in Italy and globally"--